Automated Close-Loop System for Three-Dimensional Characterization of Spatiotemporal Optical Vortex - Chen, Jian; Lu, Keyin; Cao, Qian; Wan, Chenhao; Hu, Haifeng; Zhan, Qiwen (Frontiers in Physics, 2021)
Recent rapid advances in spatiotemporal optical pulses demand accurate characterization of the spatiotemporal structure of the produced light fields. We report an automated close-loop characterization system that is capable of reconstructing the three-dimensional intensity and phase structures of spatiotemporal wavepacket illustrated by characterizing spatiotemporal optical vortex in the spatiotemporal domain. The characterization technique is based on interfering a much shorter probe pulse with different slices of the object wavepacket along the temporal axis. A close-loop control program is developed to realize full automation of the data collection and reconstruction process. Experimental results of the intensity and phase distributions show that the designed close-loop system is efficient in quantitatively characterizing the generated spatiotemporal optical vortex. Such a linear characterization system can also be extended to measure many other kinds of spatiotemporal wavepacket and may find broad applications in spatiotemporal wavepacket studies.